Efektifitas Penyuluhan tentang Adaptasi Kebiasaan Baru sebagai Upaya Pencegahan Covid-19 - Mayditania Intan Bunga Pratiwi; Nisak Zahrotun; Rozana Syntia Veronica (Universitas Ahmad Dahlan, 2022)
Coronavirus disease (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus. Efforts to increase public knowledge regarding the importance of a clean and healthy lifestyle to change people's attitudes and behavior. Community service was carried out at TPQ Al-Masyhud for two weeks in August 2020. This study aims to determine changes in knowledge, behavior, and attitudes of students at TPQ Al-Masyhud before and after being given the socialization and education of the New Normal. The educational media used were posters, videos, and booklets. The method used is a quasi-experimental method, with a pre-test post-test one-group design without a control group which was carried out twice, pre-test and after education (post-test). Education was given to 25 children through blended learning, using the WhatsApp application, and limited face-to-face meetings with 5 children. Based on the evaluation results of educational activities, the new habit adaptation protocol significantly impacted aspects of knowledge, attitudes, and behavior of TPQ Al-Masyhud students. This is evidenced by the statistical results on the post-test knowledge p = 0.001, behavior p = 0.001, and attitude p = 0.001. Participants are able to understand the causes, symptoms and be able to apply COVID-19 prevention methods in daily life, how to use a good and proper mask, how to wash hands, and ethical ways when coughing.